The composition and dynamics of the diet of the Black Vulture (Aegypius monachus) and Griffon Vulture (Gyps fulvus) in the Talysh region of Azerbaijan - S. Rajabova; T. Karimov (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія, 2021)
The composition and dynamics of the diet of the Black Vulture (Aegypius monachus L., 1766) and Griffon Vulture (Gyps fulvus Hablizl, 1783) were studied in the Talysh region of Azerbaijan in 2014-2016. For this, for 3 years, in June-July, the collection and identification of the remains of food around the nests were carried out. The remains were collected every 10 days from 15 nests of the Black Vulture and 18 nests of the Griffon Vulture. A total of 820 prey items were collected. The vultures’ diet comprised of the carcasses of 24 animal species, including 14 wild mammals, 6 domestic mammals, three reptiles and a fish. 401 prey items were collected at Griffon Vulture nests and 419 items at Black Vulture nests. 188 prey items (46.9%) were gathered in 2014, 117 (29.1%) in 2015 and 96 (24.0%) in 2016 around Griffon Vulture nests. 196 (46.7%) prey items were collected in 2014, 121 (29.0%) in 2015 and 102 (24.3%) in 2016 around Black Vulture nests. The share of the domestic animals was 17.0% (2014), 15.5% (2015) and 10.0% (2016) in the diet of the Black Vulture. The share of the wild animals was 83.0% (2014), 84.5% (2015) and 90,0% (2016), respectively. In the diet of Griffon Vulture these indicators were as follows: the share of the domestic animals was 17.0% (2014), 15.9% (2015) and 14.5% (2016), and the share of the wild animals was 83.0% (2014), 84.1% (2015) and 85.5% (2016). The research confirmed that the diet spectrum of both species in the region has narrowed over 3 years. The diet spectrum reduced by 48.0% in the Black Vulture and by 49.0% in the Griffon Vulture. It was found that the human economic activity has a significant impact on the spectrum and stability of diets of both species in the Talysh region. Therefore, in order to achieve the sustainable development of the populations of both species, it is necessary to organize regular monitoring and supplementary feeding stations. It would be desirable to make an announcement of these territories as natural monuments during the breeding season as well. The local environmental organizations and schools should be involved in the effective protection of such natural monuments.